Feasibility of bulk shipping investment - investment into supramax segment with time horizon between 2023 & 2027 - Zhuang Zhuohan (Nanyang Technological University, 2022)
The objective of this report is to determine the attractiveness of investing in the Supramax bulk carrier segment during the investment horizon 2023 - 2027. The theoretical viewpoint of both supply and demand impacts the physical and paper price, and our research revealed that market fundamentals are reflective of the current economic conditions of the shipping market. The LTAV financial model was developed to accommodate the complex valuation of a Supramax. As a Supramax can be deployed differently through the investment horizon and netting different amount of revenue, different scenarios were permutated throughout the 5-year investment period. A sensitivity analysis will be attempted to compare the results in order to search for a correlation between TCE, NPV, and IRR for the investment. While the outcome is that it is feasible to invest in Supramax within the investment horizon of 2023/2027. The approach used in this volume does, however, have its limitations in the certain areas, such as ignoring short-term volatility and not incorporating the value of real option, etc.